A critical analysis on how the application of cinematographic tools during the screenwriting process can contribute to the visualisation of post-death Christian existence in an Afrikaans film - Prinsloo, Tarryn-Tanille (University of Pretoria, 2023)
Dissertation (MA (Creative Writing))--University of Pretoria, 2022.